CLEANING OF INTERNAL SURFACE OF PIPELINE FROM CONTAMINATIONS - Зайончковський, Г.; Власов, А.; Радченко, В.; Тарасенко, Т. (Science-based technologies, 2010)
The article is sacred to researches of methods of cleaning of internal surface of pipeline from contaminations. Realization of research in this direction allowed setting the presence of effect of the cavitation cleaning of inter-nal surface of pipeline, and defining optimal time of the cavitation cleaning of pipeline which must not exceed incubation time of cavitation erosion.